Peran Guru Pendidikan Agama Islam Dalam Meningkatkan Motivasi Belajar Siswa Di Masa Pandemi - Ummah Karimah; Arya Herdian Zuhdi; Alivia Nurhabibatulkamilah; Laila Hafizhoh Muchlis (UIN Sunan Gunung Djati Bandung, 2022)
The problem with this research is the role of PAI teachers in an effort to increase learning motivation in the era of the covid-19 pandemic. The purpose of this study was to find out how the role of PAI teachers in an effort to increase learning motivation in the era of the covid-19 pandemic. The research method used is descriptive qualitative method. The procedure of this research is through interviews with PAI teachers and instruments as well as interviews with students regarding student learning motivation. The results of the research on the role of PAI teachers in increasing students' learning motivation during the COVID-19 pandemic are: (1). The role of PAI teachers in an effort to increase learning motivation and responsibility has been carried out but has not been maximized, in an effort to increase learning motivation and responsibilities the teacher acts as: corrector, inspiration, informator, organizer, motivator, initiator, facilitator, mentor, demonstrator, manager class, mediator, supervisor, and evaluator. (2) supporting factors, namely: adequate facilities and infrastructure, awareness within the students themselves, support from parents. (3) the inhibiting factors are: limited interaction between teachers and students, and unfavorable environmental conditions.